Immunoglobulin heavy chain variable region gene repertoire and B-cell receptor stereotypes in Indian patients with chronic lymphocytic leukemia. Issue 10 (2nd October 2016) - Rani, Lata; Mathur, Nitin; Gogia, Ajay; Vishnubhatla, Sreenivas; Kumar, Lalit; Sharma, Atul; Dube, Divya; Kaur, Punit; Gupta, Ritu
Abstract: In chronic lymphocytic leukemia (CLL), the geographical bias in immunoglobulin heavy-chain variable (IGHV) gene usage lead us to analyze IGHV gene usage and B-cell receptor stereotypy in 195 patients from India. IGHV3, IGHV4, and IGHV1 families were the most frequently used. 20.5% sequences had stereotyped BCR and were clustered in 12 pre-defined and 6 novel subsets. Unmutated IGHV was significantly associated with reduced time to first treatment ( p  < 0.033) and poor overall survival (OS; p  = 0.01). We observed a significant difference in OS between IGHV1, IGHV3, and IGHV4 family cases ( p  = 0.045) in early stage patients. Regarding subfamily usage, only IGHV1-69 expression was found to have statistically significant poor outcome ( p  = 0.017). Our results from the analysis of various molecular and clinical features suggest that the expression of specific IGHV gene influences the outcome in early stage CLL, and hence its assessment may be added to the clinical leukemia laboratory armamentarium.